Epidemiology of out-of-hospital pediatric airway management in the 2019 national emergency medical services information system data set. (April 2022) - Hanlin, Erin R.; Chan, Hei Kit; Hansen, Matt; Wendelberger, Barbara; Shah, Manish I.; Bosson, Nichole; Gausche-Hill, Marianne; VanBuren, John M.; Wang, Henry E.
Abstract: Objective: Airway management is an important priority in the care of critically ill children. We sought to provide updated estimates of the epidemiology of pediatric out-of-hospital airway management and ventilation interventions in the United States. Methods: We used data from the 2019 National Emergency Medical Services Information System (NEMSIS) data set. We performed a descriptive analysis of all patients < 18 years receiving one or more of the following: bag-valve-mask ventilation (BVM), tracheal intubation (TI), supraglottic airway (SGA) insertion, continuous positive airway pressure (CPAP), bilevel positive airway pressure (BiPAP) and surgical airway placement. We determined success and complication rates for each airway procedure. Results: Among 1, 148, 943 pediatric patient care encounters, airway and ventilation interventions occurred in 22, 637 (1, 970 per 100, 000 pediatric Emergency Medical Services (EMS) activations), including 64% <11 years old, 56.1% male, 16.9% cardiac arrest, 16.6% injured, and 83.9% in urban areas. Airway interventions included: BVM 3, 997 (17.7% of pediatric airway encounters), TI 3, 165 (14.0%), SGA 582 (2.6%), CPAP/BiPAP 331 (1.5%) and surgical airway 29 (0.1%). TI success was 75.2% (95% CI 73.7–76.7%) and lowest for the 0–1 month age group (56.8%; 49.2–64.2%). SGA success was 88.0% (95% CI 85.1–90.6%). Vomiting was the most common airway complication (n = 223, 1%). Conclusions: BVM and advanced airway management occur in 1 of every 51 pediatric EMS encounters. BVM is the most commonly prehospital pediatric airway management technique, followed by TI and SGA insertion. These data provide contemporary perspectives of pediatric prehospital airway management.